인천 지역 LNG G/ T발전소의 미세먼지 (PM10) 배출량 평가 및 주변 대기질 영향 분석 - 공부주(Bu-Ju Gong); 박풍모(Poong-Mo Park); 동종인(Jong-In Dong) (한국대기환경학회지, 2015)
Base on emission factors derived from National Institute of Environmental Research, Particulate matter from combined cycle power plants (CCPPs) has been estimated to be a important source of $PM_{10}$. Generally there is no serious emission of particulate matter in CCPPs. because the fuel of them is natural gas. But emission gas after long shut down season has very high dust content. Therefore $PM_{10}$ emission rate is dependent on its operation mode. In this study, particulate dispersion study for new city near CCPPs complex has performed using CALPUFF model for three case. $PM_{10}$ concentration has big difference between normal operation and 2 case start-up condition after long shutdown. In normal operating conditions, daily $0.32{\sim}0.50μg/m^3$ influence on of the surrounding area. But when 1~2 aerobic high concentration discharged conditions, average concentration is higher about $9.2{\sim}34.1μg/m^3$ than normal operating conditions.